Simulasi Proses Pengolahan Data pada Komputer Berbasis Multimedia dalam Bentuk 3 Dimensi - Ade Sukma Aulia; Shumaya Resty Ramadhani; Anggy Trisnadoli (Journal of Applied Informatics and Computing, 2019)
Computer is electronic device that are able to receive, process inputs, and produce output in the form of information.Studying data processing can be obtained from various sources ranging from studying with the experts or reading books.The learning process so far is difficult to understand if it is just an explanation or conventional teaching aids, so that students have their own constraints in understanding the lesson.Therefore media information is built in the form of simulating data processing on multimedia-based computers in 3D.The information provided in the simulation video is in accordance with the reference that has been validated by the lecturer in the field of operating system competence. In testing the Paired Sample t-Test there was an increase in the value of the quiz when using the application rather than using the book in understanding the material of the text data processing by 20.77% and the processing of sound data by 23.16%.And the survey of satisfaction with the application was carried out on 30 students and obtained an overall average yield of 91.70%.So based on the research carried out as a whole the application can be as an interactive alternative media in learning the processing of data on a computer based on the actual process that occurs on a computer in the form of 3-dimensional animation.